The impact of soft skills training on female youth employment: Evidence from a randomized experiment in Jordan - Matthew Groh; Nandini Krishnan; David McKenzie; Tara Vishwanath (IZA Journal of Labor & Development, 2016)
Employers around the world complain that youth lack the soft skills needed for success in the workplace. In response, a number of employment programs have begun to incorporate soft skills training, but to date there has been little evidence as to the effectiveness of such programs. This paper reports on a randomized experiment in Jordan in which female community college graduates were randomly assigned to a soft skills training program. Despite this program being twice as long in length as the average program in the region, and taught by a well-regarded provider, we find soft skills training does not have any significant employment impact in three rounds of follow-up surveys. We elicit expectations of academics and development professionals and reveal that these findings are novel and unexpected.
Keywords: O12; O15; J08; J16; 330; Soft skills; Youth unemployment; Randomized experiment; Expectation elicitation